(untitled) (Philosophy and Progress, 2025)
In this paper, I examine Said’s critique of Marx concerning the discourse of Orientalism. Said’s critique has raised profound debate among advocates of both Marx and Said, particularly on the question of whether Marx can be classified as an Orientalist—someone who reinforces the Orient status of the non-Western people in the global South. I will analyse the merits of Said’s allegation by examining the contrasting perspectives of Marxist and Saidian advocates. Ultimately, in the final assessment, I argue that we cannot completely deny Said’s critique of Marx. In fact, Marx’s Orientalist position in projecting the economic situation in Asia during European colonialism is explicit. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 85-124